Integrated Energy System Planning Model for Ubiquitous Power Internet of Things - Dunnan LIU; Tingting ZHANG; Hua LI; Caijuan QI; Yanxia MA; Weiqi ZHANG; Xiaofeng XU (发电技术)
One important aspect of ubiquitous power internet of things (UPIoT) construction is to realize the access of more terminal small and micro devices, make the data acquisition more massive and diversified, and realize the deep integration of data flow and energy flow, while the integrated energy system (IES) is an important value realization form of UPIoT. The IES planning for the UPIoT was studied, from the principles to be followed in the IES planning, the basic model method in the system planning and design, to the comprehensive benefit evaluation system of IES, and a complete set of IES planning system methods was put forward, aiming to provide theoretical support for the construction and implementation of the IES in China.